Students’ Perceptions of Using Google Translate in Learning English: A Mixed-Method study - Desyca Claudia; Emma Martina Pakpahan; F. Ari Anggraini Sebayang (Jurnal Impresi Indonesia, 2026)
English plays a crucial role in higher education, as many academic resources are presented in English. However, many students still face difficulties in understanding English texts due to unfamiliar vocabulary and complex sentence structures. To overcome these challenges, students often use machine translation tools, particularly Google Translate. This study aims to investigate undergraduate students’ perceptions of using Google Translate in learning English within academic contexts. This study applies a mixed-method design using an explanatory sequential approach. Quantitative data were collected through a questionnaire consisting of 25 Likert-scale items distributed to 34 undergraduate students in Medan. Qualitative data were obtained from semi-structured interviews with five selected participants to provide deeper insights. The findings reveal that Google Translate is primarily used as a vocabulary support tool. A total of 73.53% of students use it to check word meanings, while 97.06% consider it useful for learning English. However, its use decreases in more complex tasks such as paragraph and essay writing. Students also recognize its limitations, especially in grammar and contextual accuracy. Despite this, students do not entirely rely on the tool. Instead, they use it critically by verifying the results with other sources and combining them with their own language knowledge. In conclusion, Google Translate serves as a supportive tool rather than a primary learning resource. Its effectiveness depends on strategic and critical use.